2014
DOI: 10.1007/s11356-014-3098-y
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the water self-purification capacity on a river affected by organic pollution: application of chemometrics in spatial and temporal variations

Abstract: Water pollution caused by organic matter is a major global problem which requires continuous evaluation. Multivariate statistical analysis was applied to assess spatial and temporal changes caused by natural and anthropogenic phenomena along Potrero de los Funes River. Cluster analysis (CA), principal component analysis (PCA) and analysis of variance (ANOVA) were applied to a data set collected throughout a period of 3 years (2010-2012), which monitored 22 physical, chemical and biological parameters. Content … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(37 citation statements)
references
References 41 publications
3
33
0
1
Order By: Relevance
“…Depuration comprises different mechanisms such as dilution, sedimentation, reaeration, adsorption, absorption, and chemical and biological reactions, and can be evaluated by the same mathematical model (Bahadur et al, 2013, González et al, 2014. Water quality models are essential tools for the development of planning and management measures for water resources in river basins (Panagopoulos et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Depuration comprises different mechanisms such as dilution, sedimentation, reaeration, adsorption, absorption, and chemical and biological reactions, and can be evaluated by the same mathematical model (Bahadur et al, 2013, González et al, 2014. Water quality models are essential tools for the development of planning and management measures for water resources in river basins (Panagopoulos et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…More and more attention has been paid to surface water quality, as it is strongly relevant to human lives and public health [1,2]. However, as surface water quality is controlled by both natural factors (hydrological and meteorological conditions) and human influences (urban, industrial and agricultural activities), decision makers are facing with significant difficulties the problem of how to manage surface water quality [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…It is observed that most parameters especially As, Cr, Cu, Pb, Zn and Mn have a high standard deviation and a high change interval. This situation indicates that heavy metal concentration varies depending on anthropogenic and natural factors (González et al, 2014). Mean concentration of Fe, Mn and Zn was chancing between 353-594 µg/L, 63-353 µg/L and 30-50 µg/L, respectively.…”
Section: Basic Statistics Of Heavy Metalsmentioning
confidence: 89%